SEGREGASI SOSIAL DALAM NOVEL OTOBIOGRAFI I KNOW WHY THE CAGED BIRD SINGS KARYA MAYA ANGELOU - LAMBI, ALFRIDO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research, entitled â€œSosial Segregation in I Know Why the Caged Bird Sings by Maya Angelou focuses on the sosiological issue as an extrinsic aspect in literature particularly in prose. The writer decides to use the autobiographical novel by Maya Angelou as the object of this research because of the strong theme and atmosphere of sosiological issue depicted in it. The problem of this research is the social segregation as a discriminative action by one superior social community toward another inferior social community. The writer uses the theory of sociology in literature by Alan Swingewood as the basis to analyze the problem of this research. The result of this research shows that Maya Angelou used her childhood life story through inter-character dialogues and her narrative to depict the social segregation in her autobiographical novel which is also her social criticism. Through this research, the readers are expected to understand about the segregation and discriminative actions particularly in racism, because those actions still exist even in this modern era. Â  Keywords : Autobiographical Novel, Maya Angelou, Social Segregation, Discrimination